3D printing device and method based on ceramic wires

By combining silk material forming and ceramic silk 3D printing technology, the printing of high -precision single/composite silk composite ceramic materials is achieved, solving the problem of lack of neutral and mechanical properties in existing technology, and achieved excellent mechanics. And biological performance.

CN119328872APending Publication Date: 2025-01-21SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411469080.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing 3D printing technology is difficult to achieve the printing of high-precision single/multifilament composite ceramic materials, especially at the micron level, and there is a problem of insufficient neutrality and mechanical properties of fibers.

Method used

Using ceramic filament-based 3D printing devices and methods, the filament forming and ceramic filament 3D printing are combined to ensure the neutrality and high precision of fiber composite ceramic materials through the filament forming unit and ceramic filament 3D printing unit. Print.

Benefits of technology

Realize the printing of high -precision continuous fiber composite ceramic material brackets, ensure the preparation of composite biological ceramic stents with good fibers, excellent mechanical performance and biomedicity. Ceramic printing problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328872A_ABST
    Figure CN119328872A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of 3D printing equipment, and particularly relates to a 3D printing device and method based on ceramic wires. The 3D printing device comprises a wire forming unit, and the wire forming unit is used for continuously supplying fiber composite ceramic wires and comprises a storage barrel, an extrusion device and an extrusion barrel. The ceramic wire 3D printing unit is used for extruding and printing fiber composite ceramic wires from the wire forming unit to form a composite ceramic support and comprises a wire feeding mechanism and a wire softening printing mechanism, the wire feeding mechanism is used for winding the fiber composite ceramic wires from the wire forming unit, and the wire softening printing mechanism is used for softening the fiber composite ceramic wires from the wire forming unit. And after being softened by a softening solution, the composite ceramic stent is extruded and printed to form the composite ceramic stent. The continuous fiber composite ceramic wire is combined with a ceramic wire 3D printing device through ceramic wire forming, and the integrated design from wire forming to 3D printing of the continuous fiber reinforced biological ceramic scaffold is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing equipment, and in particular relates to a 3D printing device and method based on ceramic filaments. Background Art

[0002] 3D printing, as an additive manufacturing technology, can be used to manufacture bioceramic scaffolds. It is easy to control the internal structure, shape, porosity and pore size of the scaffolds, and can produce various implants with complex structures for the treatment of bone defects, providing opportunities for the application of bioceramic scaffolds in the field of bone tissue engineering. Currently, the commonly used 3D printing methods include direct ink writing, digital light processing, stereolithography, fused deposition modeling and selective laser sintering.

[0003] Among them, direct ink writing is the most commonly used ideal method for preparing continuous fiber reinforced ceramic composites with complex geometric shapes. However, when this method is used to print continuous fiber composite ceramic brackets, the fluidity of the slurry is required to be high. Poor slurry fluidity may lead to insufficient coating between the fiber and the slurry, thereby affecting the centering of the fiber. In addition, during the extrusion molding of the composite material, due to the action of the pulling force, the fibers in the printed filaments will be offset. Under the action of external force, the fibers of the composite material will peel off and fall out of the matrix, the matrix material will break, and the bending strength of the composite material will be low; digital light processing and stereolithography methods have limitations in material selection, and the equipment and operating costs are high. The stability and post-processing complexity of the ceramic slurry are relatively large. After printing, post-processing steps are usually required, but the post-processing process will cause the ceramic bracket to deform, shrink and crack, thereby destroying the integrity of the composite material, affecting the mechanical properties and density of the composite body; fused deposition continuous fiber reinforced composite 3D printers are mostly used for resin polymers. The polymer filaments are melted by heating and extruded by a nozzle. However, ceramic solid particles need to be mixed with the liquid phase to form a ceramic slurry before they can be fed and formed, and the reinforcing materials are mostly continuous carbon fiber bundles or glass fiber bundles (usually 1000-5000 strands), which are not suitable for the manufacture of high-precision single / multifilament continuous fiber-reinforced ceramic-based composite brackets; selective laser sintering combines ceramic powder materials and binders, and the laser selectively sinters the mixed powder in layers to obtain a formed part, and then post-processes the resulting formed part, but selective laser sintering technology cannot prepare fiber-reinforced ceramic composite material blanks.

[0004] In 2014, Mark Forged, a US company, developed a 3D printer for continuous fiber reinforced thermoplastic composites. The printer used thermoplastics to pre-impregnate the continuous fiber matrix, but the fiber content and the interface between the fiber and the matrix could not be controlled during the printing process. Since the original single-layer print head of the printer could not accurately control the temperature, there were still certain limitations in the molding of composite material structures. In addition, Tian Xiaoyong et al. developed a 3D printer with a double-layer print head. Continuous carbon fiber reinforced SnPb-based composites were prepared using prepreg and pretreated continuous carbon fiber bundles as raw materials. During the printing process, the molten filaments and continuous fiber bundles were sent from the upper part of the device to the heating block to form a composite monofilament. The composite monofilament was pulled out and sent to the lower heating block. During the printing process, the composite monofilament was cooled to ensure uniform molding of the profile. However, the printing device is prone to nozzle clogging, and the matrix flows downward along the fiber, making it difficult to form. In summary, the above-mentioned 3D printers cannot be used for high-precision 3D printing of single / multi-filament composite ceramic materials at the micron level. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a 3D printing device and method based on ceramic wire. By combining wire forming and ceramic wire 3D printing device, the 3D printing technology and method of continuous fiber composite ceramic materials were first invented. The method can ensure the centering of the fiber composite ceramic material 3D printing process; print out high-precision continuous fiber composite ceramic material scaffolds; and realize the preparation of composite bioceramic scaffolds with controllable precision, adjustable pore structure, good fiber centering performance, and excellent mechanical and biological properties from both the 3D printing device and the process. It can solve the problem that the current 3D printing technology cannot be used for the printing of single-filament composite ceramics at the micron level, and its application in biological fields such as bone tissue engineering provides broad prospects.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The first object of the present invention is to provide a 3D printing device based on ceramic filaments, comprising:

[0008] A wire forming unit is used to continuously supply fiber composite ceramic wires. The wire forming unit includes a storage barrel, an extrusion device and an extrusion barrel. One end of the storage barrel is connected to a power mechanism, and the other end is provided with a discharge port. The discharge port is connected to the extrusion device, and the extrusion device is connected to the extrusion barrel. The upper end of the extrusion barrel is provided with a fiber inlet, and the lower end is provided with a nozzle.

[0009] A ceramic wire 3D printing unit, the ceramic wire 3D printing unit is used to extrude and print the fiber composite ceramic wire from the wire forming unit to form a composite ceramic bracket, the ceramic wire 3D printing unit includes: a wire feeding mechanism and a wire softening printing mechanism, the wire feeding mechanism is used to wind the fiber composite ceramic wire from the wire forming unit and convey it to the wire softening printing mechanism; the wire softening printing mechanism is provided with a softening liquid, and after being softened by the softening liquid, it is extruded and printed to form a composite ceramic bracket; the wire feeding mechanism includes a winder, a conduit and a feed wheel, the winder is used to wind the fiber composite ceramic wire from the wire forming unit, one end of the conduit is rotatably connected to the winder, and the other end is rotatably connected to the feed wheel, and the feed wheel is used to convey the fiber composite ceramic wire to the wire softening printing mechanism.

[0010] Furthermore, the wire softening printing mechanism comprises a softening liquid reservoir, a softening tank and a printing nozzle, the softening liquid reservoir is connected to the softening tank through a softening liquid pipeline, and the printing nozzle is fixedly arranged below the softening tank.

[0011] Furthermore, an extension portion is provided at the lower end of the softening liquid pipeline, a liquid inlet is provided at the lower end of the extension portion, the liquid inlet is located above the softening tank, and a flow control valve is provided on the softening liquid pipeline.

[0012] Furthermore, a shearing device is provided below the outside of the printing nozzle, and a three-axis motion platform is provided below the shearing device.

[0013] Furthermore, a fixing block is provided at the upper end of the softening liquid storage tank, and the fixing block is also connected to a slide rail.

[0014] A second object of the present invention is to provide a method for printing a ceramic bracket, which is performed using the above-mentioned 3D printing device, comprising the following steps:

[0015] The polyvinyl alcohol and the solvent are mixed and heated in a water bath until the polyvinyl alcohol is completely dissolved, thereby obtaining a solution A.

[0016] After the hydroxyapatite whiskers and spherical hydroxyapatite are evenly mixed, solution A is added and mixed evenly to obtain a ceramic slurry.

[0017] The ceramic slurry is added into the storage barrel, and then the fiber is fed into the nozzle from the fiber inlet. The ceramic slurry in the storage barrel is transported to the extrusion device under the action of the power mechanism. Then, under the extrusion action of the extrusion device, the ceramic slurry is transported to the extrusion barrel through the discharge port. After the ceramic slurry and the fiber are infiltrated in the nozzle and the slurry evenly covers the fiber, the fiber composite ceramic wire is obtained after continuous extrusion through the nozzle.

[0018] The fiber composite ceramic wire is wound and stored by a winder, and the wound and stored ceramic wire is continuously transported to the feed wheel through a catheter. The continuous fiber composite ceramic wire is transported to the wire softening printing mechanism by the feed wheel, softened by the softening liquid in the wire softening printing mechanism, and then extruded and printed according to the printing path to form a continuous composite ceramic bracket blank.

[0019] The composite ceramic bracket blank is dried at room temperature and then dried at 50° C. to 70° C. to obtain a continuous fiber composite ceramic bracket.

[0020] Furthermore, the mass ratio of the polyvinyl alcohol to the solvent is 10:90 to 15:85, and the solvent is water.

[0021] Furthermore, the length of the hydroxyapatite whisker is 100 μm to 200 μm, the aspect ratio is 10 to 100, the diameter of the spherical hydroxyapatite is less than 100 nm, the mass ratio of the hydroxyapatite whisker to the spherical hydroxyapatite is 3:7 to 10:0; and the mass fraction of polyvinyl alcohol in the ceramic slurry is 15% to 5%.

[0022] Furthermore, the diameter of the fiber composite ceramic wire is 600 μm to 1400 μm.

[0023] Furthermore, the softening liquid is a PVA aqueous solution, a glycerol aqueous solution, an ethanol aqueous solution or a carboxymethyl cellulose aqueous solution; the drying time at room temperature is 1 h to 2 h, and the drying time at 50° C. to 70° C. is 2 h to 4 h.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention combines wire forming and ceramic wire 3D printing. On the one hand, through the wire forming process, the present invention can ensure the uniformity of wire diameter, continuous fiber feeding, and centering. Uniform wire diameter is crucial to the subsequent 3D printing process. It can effectively prevent blockage or uneven spraying during the printing process and ensure the accuracy and quality of the printed product. On the other hand, the 3D printing device developed by the present invention has a high degree of flexibility and adjustability, and can realize the printing of ceramic wires of different diameters and different compositions. At the same time, it can ensure that the accuracy of the printing scaffold is controllable, and the pore structure of the composite bioceramic scaffold can be adjusted according to needs. By adjusting printing parameters, such as nozzle diameter, printing speed, and material ratio, it is possible to achieve precise control of the diameter, porosity, and pore size of the scaffold filament, thereby meeting the needs of different biological applications. This method can ensure the centering of the fiber composite ceramic material 3D printing process; print out high-precision continuous fiber composite ceramic material scaffolds; and achieve the preparation of composite bioceramic scaffolds with controllable precision, adjustable pore structure, good fiber centering performance, and excellent mechanical and biological properties from the two aspects of 3D printing device and process. It can solve the printing problem of single-filament composite ceramics that cannot be solved by current 3D printing technology, and its application in biological fields such as bone tissue engineering provides broad prospects.

[0026] (2) The wire softening printing mechanism used in the present invention ensures the controllable softening, shaping and printing of the wire by quantitatively adding a small amount of softening liquid. The wire feeding mechanism used realizes the continuous, uniform and accurate delivery of the ceramic wire to the print head to meet the requirements of high-precision and high-quality printing or processing.

[0027] (3) The present invention realizes the preparation of composite bioceramic scaffolds with controllable precision, adjustable pore structure, good fiber centering performance, and excellent mechanical and biological properties from two aspects of 3D printing device and process. The mechanical properties and degradability of the prepared bioceramic scaffolds can be controlled by adjusting the process such as different ratios, different printing spacings, and different printing diameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic structural diagram of a 3D printing device based on ceramic filaments according to the present invention.

[0029] Description of reference numerals:

[0030] 1. Power mechanism, 2. Storage barrel, 3. Extrusion device, 4. Feeding port, 5. Fiber composite ceramic wire, 6. Nozzle, 7. Extrusion barrel, 8. Fiber, 9. Wire inlet, 10. Fixed block, 11. Slide rail, 12. Softening liquid storage, 13. Softening liquid, 14. Liquid outlet, 15. Softening liquid pipeline, 16. Flow control valve, 17. Liquid inlet, 18. Softening tank, 19. Printing nozzle, 20. Three-axis motion platform, 21. Shearing device, 22. Feed wheel, 23. Catheter, 24. Winder, 25. Connecting joint.

[0031] Figure 2 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 2 of the present invention. Figure 2 In the figure, a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire.

[0032] Figure 3 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 3 of the present invention. Figure 3 In the figure, a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire.

[0033] Figure 4 This is a macroscopic image of the continuous PGA fiber reinforced ceramic composite bracket prepared in Example 3 of the present invention. Figure 4 a is a physical picture of the prepared continuous PGA fiber reinforced ceramic composite scaffold, b is a super depth of field picture of the cross section of the continuous PGA fiber reinforced ceramic composite scaffold × 75 times, and c is a super depth of field picture of the cross section of the continuous PGA fiber reinforced ceramic composite scaffold × 200 times.

[0034] Figure 5 This is a macroscopic image of the continuous PGA fiber reinforced ceramic composite bracket prepared in Example 4 of the present invention.

[0035] Figure 6 This is a test diagram of the mechanical properties of the PGA fiber composite ceramic wire prepared in Example 5 of the present invention. Figure 6 In the figure, a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire.

[0036] Figure 7 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 6 of the present invention. Figure 7 In the figure, a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire.

[0037] Figure 8 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 1 of the present invention when immersed in Tris-HCl.

[0038] Fig. 9 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 2 of the present invention when immersed in Tris-HCl.

[0039] Fig.10 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 3 of the present invention when immersed in Tris-HCl.

[0040] Fig.11 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 5 of the present invention when immersed in Tris-HCl.

[0041] Fig.12 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 6 of the present invention when immersed in Tris-HCl. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0044] Existing continuous fiber reinforced composite scaffolds are mostly printed by direct ink writing method. The poor fluidity of ceramic slurry leads to insufficient coating of fibers and ceramic materials during printing. As the printing direction changes, there is still a problem of difficulty in compounding fiber filaments and ceramic slurry. For example, the fiber filaments cannot ensure neutrality, and the unique viscosity of ceramic slurry also affects the molding of the scaffold; when the viscosity of the slurry is too low, the bioceramic scaffold cannot be molded, or exhibits poor mechanical properties after molding. When the viscosity of the slurry is too high, it will cause difficulty in extrusion of the slurry, thereby reducing the molding accuracy of the scaffold. In addition, due to the high solid content, the flow characteristics of the ceramic slurry are affected, which leads to the weakening of the adhesion between the continuous fiber and the ceramic substrate, thereby seriously reducing the mechanical properties of the composite material. If the extruded slurry and filaments cannot be cured in time, fiber eccentricity is likely to occur in the subsequent molding process, and the scaffold layers are prone to collapse, resulting in poor mechanics. Therefore, how to prepare continuous fiber composite ceramic scaffolds with excellent mechanical properties and degradation properties through 3D printers remains a challenge.

[0045] Based on the above problems, on the one hand, the present invention provides a 3D printing device based on ceramic filaments, such as Figure 1 As shown, including:

[0046] A wire forming unit, which is used to continuously supply fiber composite ceramic wires, comprises a storage barrel 2, an extrusion device 3 and an extrusion barrel 7. One end of the storage barrel 2 is connected to a power mechanism 1, and the other end is provided with a discharge port 4, the discharge port is communicated with the extrusion device 3, the extrusion device 3 is communicated with the extrusion barrel 7, and a fiber inlet 9 is provided at the upper end of the extrusion barrel 7, and a nozzle 6 is provided at the lower end.

[0047] A ceramic wire 3D printing unit, the ceramic wire 3D printing unit is used to extrude and print the fiber composite ceramic wire 5 from the wire forming unit to form a composite ceramic bracket, the ceramic wire 3D printing unit includes: a wire feeding mechanism and a wire softening printing mechanism, the wire feeding mechanism is used to wind the fiber composite ceramic wire 5 from the wire forming unit and convey it to the wire softening printing mechanism; the wire softening printing mechanism is provided with a softening liquid 13, after being softened by the softening liquid 13, it is extruded and printed to form a composite ceramic bracket; the wire feeding mechanism includes a winder 24, a conduit 23 and a feed wheel 22, the winder 24 is used to wind the fiber composite ceramic wire 5 from the wire forming unit, one end of the conduit 23 is rotatably connected to the winder 24, and the other end is rotatably connected to the feed wheel 22, and the feed wheel 22 is used to convey the fiber composite ceramic wire 5 to the wire softening printing mechanism.

[0048] The present invention combines wire forming and ceramic wire 3D printing. On the one hand, through the wire forming process, the present invention can ensure the uniformity of wire diameter, continuous fiber feeding, and centering. Uniform wire diameter is crucial to the subsequent 3D printing process. It can effectively prevent blockage or uneven spraying during the printing process, and ensure the accuracy and quality of the printed product; on the other hand, the 3D printing device developed by the present invention has a high degree of flexibility and adjustability, and can realize the printing of ceramic wires of different diameters and different compositions. At the same time, it can ensure that the accuracy is controllable during the printing process of the stent, and can adjust the pore structure of the composite bioceramic stent according to demand. By adjusting printing parameters, such as nozzle diameter, printing speed, and material ratio, etc., it is possible to achieve precise control of the stent wire diameter, porosity, and pore size, thereby meeting the needs of different biological applications.

[0049] The present invention combines wire forming and ceramic wire 3D printing devices, and is the first to invent 3D printing technology and methods for continuous fiber composite ceramic materials. The method can ensure the centering of the fiber composite ceramic material 3D printing process; print out high-precision continuous fiber composite ceramic material scaffolds; and achieve the preparation of composite bioceramic scaffolds with controllable precision, adjustable pore structure, good fiber centering performance, and excellent mechanical and biological properties from both the 3D printing device and the process. It can solve the problem that the current 3D printing technology cannot be used for the printing of single-filament composite ceramics, and its application in biological fields such as bone tissue engineering provides broad prospects.

[0050] In a specific embodiment, the power mechanism 1 is an air compressor, which provides power to feed the ceramic slurry in the storage barrel 2 into the extrusion device 3. The extrusion device 3 is a micro screw extruder, which can evenly and continuously pass the ceramic slurry into the nozzle 6. The fiber 8 enters from the fiber inlet 9, and the fiber 8 and the ceramic slurry are fully infiltrated inside the nozzle 6, and the slurry evenly covers the fiber. Through a nozzle with a certain structure and size (the diameter of the nozzle is 800μm to 1700μm), continuous fiber composite ceramic wires 5 with different diameters and compositions are prepared.

[0051] In a specific embodiment, the wire softening printing mechanism includes a softening liquid reservoir 12 , a softening tank 18 and a printing nozzle 19 . The softening liquid reservoir 12 is connected to the softening tank 18 through a softening liquid pipeline 15 , and the printing nozzle 19 is fixedly arranged below the softening tank 18 . The softening liquid reservoir 12 is used to store the softening liquid 13. A fixed block 10 is provided at the upper end of the softening liquid reservoir 12. The lower end of the fixed block 10 is connected to the upper end of the softening liquid reservoir 12. The fixed block 10 is also connected to a slide rail 11. The side wall of the fixed block 10 is fixed on the slide rail 11. The slide rail 11 is a slide rail of a 3D printer. The slide rail 11 can be used to perform printing path movement during the molding process. A liquid outlet 14 is provided at the lower end of the softening liquid reservoir 12. The liquid outlet 14 is connected to a softening liquid pipeline 15. A flow control valve 16 is provided on the softening liquid pipeline 15. The flow control valve 16 controls a trace amount (0.01 mL / min to 0.09 mL / min) of softening liquid 13 to be added to the softening tank 18 at a liquid delivery speed of 0.002 mL / min to 0.500 mL / min.

[0052] In a specific embodiment, the winder 24 is used to wind the fiber composite ceramic wire from the wire forming unit, and the conduit 23 is connected to the winder 24 through the connecting joint 25. The conduit 23 accurately transports the fiber composite ceramic wire 5 to the softening tank 18 through the feeding wheel 22 to achieve continuous wire feeding; the lower part of the softening tank 18 is connected to the printing nozzle 19. A shearing device 21 is arranged below the outside of the nozzle 19, and a three-axis motion platform 20 is arranged directly below the printing nozzle 19. The diameter of the printing nozzle 19 is 800μm to 1700μm. The forming and printing part moves according to the printing path, so that the composite wire is continuously formed and printed on the printing platform through the printing nozzle 19, thereby realizing the printing of the desired path and shape product.

[0053] In a specific embodiment, the lower end of the softening liquid pipeline 15 is provided with an extension portion, and the lower end of the extension portion is provided with a liquid inlet 17, and the liquid inlet 17 is located above the softening tank 18. The softening liquid 13 is added into the softening tank 18 through the liquid inlet 17.

[0054] On the other hand, the present invention provides a method for printing a ceramic bracket, using the above-mentioned 3D printing device to print a ceramic bracket, wherein the ceramic material matrix uses whisker-like HA (hydroxyapatite) and spherical HA, and the fiber uses PGA (polyglycolic acid) fiber with a diameter of 0.03mm to 0.04mm, comprising the following steps:

[0055] S1. Mix polyvinyl alcohol (PVA) and deionized water in a mass ratio of 10:90 to 15:85, and soak at room temperature for 12 hours to obtain a mixed solution.

[0056] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0057] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 3:7 to 10:0, and mix them to obtain a mixed powder for later use.

[0058] S4. According to the PVA content of 15% to 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 3 minutes to 10 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged in a centrifuge at a speed of 2000rpm to 3000rpm for 10 minutes to 15 minutes, and then the slurry is placed in a vacuum environment for 1 minute to 5 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0059] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 under an air pressure of 0.01MPa to 1.00MPa through the power mechanism 1. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.05mL / min to 0.80mL / min, and then transported to the nozzle 6; the PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. According to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 800μm to 1700μm, and continuous PGA fiber composite ceramic wires of different diameters and components are obtained, and the wire diameter is 600μm to 1400μm.

[0060] S6, prepare softening liquid 13: prepare PVA aqueous solution (PVA content is 0wt.% ~ 20wt.%), glycerol aqueous solution (glycerol content is 40wt.% ~ 50wt.%), ethanol aqueous solution (ethanol content is 0wt.% ~ 100wt.%) or carboxymethyl cellulose aqueous solution (carboxymethyl cellulose content is 1wt.% ~ 5wt.%), store them separately in canned sterilized sealed containers, avoid direct sunlight and high temperature, and place them in a cool and dry environment to ensure the stability and effectiveness of the softening liquid for subsequent use; add the softening liquid 13 into the softening liquid reservoir 12.

[0061] S7. The continuous PGA fiber composite ceramic wire in a semi-wet state (25 minutes after the wire is formed) is introduced into the ceramic wire 3D printing unit, wound and stored by the winder 24, and the wound and stored ceramic wire is continuously transported to the feed wheel 22 through the conduit 23. The feed wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2 mm / s, thereby ensuring the controllable softening, forming and printing of the wire.

[0062] S8. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0063] S9. Evenly apply a layer of PVA solution (25wt.% PVA aqueous solution) on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic wire into a bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the amount of softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0064] S10, drying the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then drying it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then printing the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0065] It should be noted that in the S5 process, the formed continuous PGA fiber composite ceramic wire can also be stored in a container for 25 minutes, sealed and stored in a cool place to avoid direct sunlight; or a certain traction force (0.05N) is applied to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, dry it at room temperature, and then soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, and then introduce it into the ceramic wire 3D printing unit, wind it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23.

[0066] The wire softening printing mechanism used in the present invention ensures the controllable softening, shaping and printing of the wire by quantitatively adding a trace amount of softening liquid. The wire feeding mechanism used realizes continuous, uniform and accurate delivery of the ceramic wire to the print head to meet the requirements of high-precision and high-quality printing or processing.

[0067] The present invention realizes the preparation of composite bioceramic scaffolds with controllable precision, adjustable pore structure, good fiber centering performance, and excellent mechanical and biological properties from two aspects of 3D printing device and process. The mechanical properties and degradability of the prepared bioceramic scaffold can be controlled by adjusting the process (different ratios, different printing spacings, different printing diameters). This innovation can solve the printing problem of single-filament composite ceramics that cannot be solved by current 3D printing technology, and its application in biological fields such as bone tissue engineering provides broad prospects.

[0068] The invention is further described below through specific examples.

[0069] Example 1

[0070] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0071] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0072] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0073] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 3:7 and mix them to obtain a mixed powder for later use.

[0074] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 3-10 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0075] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.6 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, and the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1300 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 1000 μm.

[0076] S6. Prepare softening liquid 13: prepare a PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store it in a canned sterilized sealed container, avoid direct sunlight and high temperature, and place it in a cool and dry environment to ensure the stability and effectiveness of the softening liquid for subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0077] S7. The continuous PGA fiber composite ceramic wire in a semi-wet state (25 minutes after the wire is formed) is introduced into the ceramic wire 3D printing unit, wound and stored by the winder 24, and the wound and stored ceramic wire is continuously transported to the feed wheel 22 through the conduit 23. The feed wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2 mm / s, thereby ensuring the controllable softening, forming and printing of the wire.

[0078] S8. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0079] S9. Evenly apply a layer of PVA solution (25wt.% PVA aqueous solution) on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, and a continuous fiber composite ceramic bracket blank is obtained.

[0080] S10, drying the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then drying it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then printing the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0081] Example 2

[0082] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0083] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0084] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0085] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 4:6 and mix them to obtain a mixed powder for later use.

[0086] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 8 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0087] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.6 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, and the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1300 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 1000 μm.

[0088] S6. Store the formed continuous fiber composite ceramic wire in a container for 25 minutes, seal it and store it in a cool place, away from direct sunlight.

[0089] S7. Apply a certain pulling force (0.05N) to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, and dry it at room temperature.

[0090] S8, prepare softening liquid 13: prepare PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store in a canned sterilized sealed container, avoid direct sunlight and high temperature, place in a cool and dry environment to ensure the stability and effectiveness of the softening liquid, and facilitate subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0091] S9. Soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, then introduce it into the ceramic wire 3D printing unit, wind it up and store it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23. The feeding wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2mm / s, thereby ensuring the controllable softening, shaping and printing of the wire.

[0092] S10. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the liquid outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0093] S11. A layer of PVA solution (25wt.% PVA aqueous solution) is evenly applied on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0094] S12. Dry the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then dry it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then print the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0095] Example 3

[0096] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0097] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0098] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0099] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 7:3 and mix them to obtain a mixed powder for later use.

[0100] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 8 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0101] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.6 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, and the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1300 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 1000 μm.

[0102] S6. Store the formed continuous fiber composite ceramic wire in a container for 25 minutes, seal it and store it in a cool place, away from direct sunlight.

[0103] S7. Apply a certain pulling force (0.05N) to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, and dry it at room temperature.

[0104] S8, prepare softening liquid 13: prepare PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store in a canned sterilized sealed container, avoid direct sunlight and high temperature, place in a cool and dry environment to ensure the stability and effectiveness of the softening liquid, and facilitate subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0105] S9. Soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, then introduce it into the ceramic wire 3D printing unit, wind it up and store it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23. The feeding wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2mm / s, thereby ensuring the controllable softening, shaping and printing of the wire.

[0106] S10. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the liquid outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0107] S11. A layer of PVA solution (25wt.% PVA aqueous solution) is evenly applied on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0108] S12. Dry the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then dry it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then print the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0109] Example 4

[0110] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0111] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0112] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0113] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 7:3 and mix them to obtain a mixed powder for later use.

[0114] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 8 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0115] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.3 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1000 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 700 μm.

[0116] S6. Store the formed continuous fiber composite ceramic wire in a container for 25 minutes, seal it and store it in a cool place, away from direct sunlight.

[0117] S7. Apply a certain pulling force (0.05N) to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, and dry it at room temperature.

[0118] S8, prepare softening liquid 13: prepare PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store in a canned sterilized sealed container, avoid direct sunlight and high temperature, place in a cool and dry environment to ensure the stability and effectiveness of the softening liquid, and facilitate subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0119] S9. Soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, then introduce it into the ceramic wire 3D printing unit, wind it up and store it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23. The feeding wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2mm / s, thereby ensuring the controllable softening, shaping and printing of the wire.

[0120] S10. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the liquid outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0121] S11. A layer of PVA solution (25wt.% PVA aqueous solution) is evenly applied on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0122] S12. Dry the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then dry it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then print the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0123] Example 5

[0124] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0125] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0126] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0127] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 9:1 and mix them to obtain a mixed powder for later use.

[0128] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 8 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0129] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.6 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, and the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1300 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 1000 μm.

[0130] S6. Store the formed continuous fiber composite ceramic wire in a container for 25 minutes, seal it and store it in a cool place, away from direct sunlight.

[0131] S7. Apply a certain pulling force (0.05N) to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, and dry it at room temperature.

[0132] S8, prepare softening liquid 13: prepare PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store in a canned sterilized sealed container, avoid direct sunlight and high temperature, place in a cool and dry environment to ensure the stability and effectiveness of the softening liquid, and facilitate subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0133] S9. Soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, then introduce it into the ceramic wire 3D printing unit, wind it up and store it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23. The feeding wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2mm / s, thereby ensuring the controllable softening, shaping and printing of the wire.

[0134] S10. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the liquid outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0135] S11. A layer of PVA solution (25wt.% PVA aqueous solution) is evenly applied on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0136] S12. Dry the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then dry it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then print the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0137] Example 6

[0138] A 3D printing method for a continuous fiber composite ceramic bracket using the above 3D printing device comprises the following steps:

[0139] S1. PVA and deionized water were mixed in a mass ratio of 15:85, and immersed at room temperature for 12 hours to obtain a mixed solution.

[0140] S2. In a water bath, slowly heat the mixed solution to 60°C and keep it warm for 4 hours. Then heat it in a water bath and slowly heat it to 95°C and keep it warm. Continue stirring for 4 hours until the PVA is completely dissolved in deionized water. After cooling the dissolved PVA solution to room temperature, obtain solution A, can it into a sterilized container, seal it with sealing film and store it for later use.

[0141] S3. Select HA whiskers with a length range of 100 μm to 200 μm and an aspect ratio of about 10 to 100; the diameter of the spherical HA is less than 100 nm, weigh the whisker HA and the spherical HA in a mass ratio of 10:0 and mix them to obtain a mixed powder for later use.

[0142] S4. According to the PVA content of 5%, the mixed powder in S3 and the solution A in S2 are mixed, and ultrasonic stirring is performed for 3-10 minutes to make the mixture uniform to form a slurry. The slurry is centrifuged at a speed of 2200 rpm in a centrifuge for 12 minutes, and then the slurry is placed in a vacuum environment for 2 minutes to remove bubbles. The steps of centrifugation and vacuum degassing are repeated three times until most of the bubbles are removed to obtain a ceramic slurry.

[0143] S5. After the PGA fiber is fed into the nozzle 6 from the fiber inlet 9, the ceramic slurry is then added into the storage barrel 2. The ceramic slurry is transported from the storage barrel 2 to the extrusion device 3 through the power mechanism 1 at an air pressure of 0.6 MPa. Under the extrusion action of the screw of the extrusion device 3, the ceramic slurry is transported to the extrusion barrel 7 through the discharge port 4 at an extrusion speed of 0.6 mL / min, and then transported to the nozzle 6. The PGA fiber is pre-penetrated into the nozzle 6 from the set fiber inlet 9, and the ceramic slurry and the fiber are infiltrated in the nozzle 6, and the slurry evenly covers the fiber and is continuously extruded through the nozzle 6. Then, according to a certain structure and size of the nozzle 6, it is extruded and formed. The diameter of the nozzle 6 is 1300 μm, and a continuous PGA fiber composite ceramic wire is obtained, and the wire diameter is 1000 μm.

[0144] S6. Store the formed continuous fiber composite ceramic wire in a container for 25 minutes, seal it and store it in a cool place, away from direct sunlight.

[0145] S7. Apply a certain pulling force (0.05N) to both ends of the formed PGA continuous fiber composite ceramic wire to ensure the stability and linearity of the wire, and dry it at room temperature.

[0146] S8, prepare softening liquid 13: prepare PVA aqueous solution (PVA content in the PVA aqueous solution is 20wt.%), store in a canned sterilized sealed container, avoid direct sunlight and high temperature, place in a cool and dry environment to ensure the stability and effectiveness of the softening liquid, and facilitate subsequent use; add the softening liquid 13 into the softening liquid storage tank 12.

[0147] S9. Soak the dried PGA continuous fiber composite ceramic wire in a PVA aqueous solution (the PVA content in the PVA aqueous solution is 15wt.%) for 10 minutes, then introduce it into the ceramic wire 3D printing unit, wind it up and store it through the winder 24, and continuously transport the wound and stored ceramic wire to the feed wheel 22 through the conduit 23. The feeding wheel 22 continuously, evenly and accurately transports the ceramic wire stored in the wire storage tube 25 to the printing nozzle 19 at a wire feeding speed of 2mm / s, thereby ensuring the controllable softening, shaping and printing of the wire.

[0148] S10. At this time, the softening liquid 13 in the wire softening printing mechanism is delivered to the softening tank 18 from the liquid outlet 14 of the softening liquid storage device 12 through the softening liquid pipeline 15, wherein the flow control valve controls the softening liquid to be added to the softening tank 18 at a delivery speed of 0.30 mL / min to soften the ceramic wire.

[0149] S11. A layer of PVA solution (25wt.% PVA aqueous solution) is evenly applied on the three-axis motion platform 20. The printing nozzle 19 in the wire softening printing mechanism prints the softened continuous PGA fiber composite ceramic bracket according to the printing path. During the printing process, the flow control valve 16 is used to adjust the trace softening liquid in the softening tank 18 to 0.06mL / min. The ceramic wire is continuously and smoothly printed to avoid breakage or deformation, thereby obtaining a continuous fiber composite ceramic bracket blank.

[0150] S12. Dry the continuous fiber composite ceramic bracket blank at room temperature for 1 hour, and then dry it in a drying oven at 50° C. for 2 hours to obtain a continuous fiber composite ceramic bracket, and then print the continuous fiber composite ceramic bracket by combining a ceramic wire forming device and a ceramic wire 3D printing device.

[0151] The properties of the PGA fiber composite ceramic wires prepared in Examples 1 to 6 were tested, and the results were as follows:

[0152] Figure 2 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 2 of the present invention. Figure 2 a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire. Figure 2 As shown, it can be seen that the maximum load that the wire prepared under this condition can withstand is 0.92N.

[0153] Figure 3 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 3 of the present invention. Figure 3 a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire. Figure 3 As shown, it can be seen that the maximum load that the wire prepared under this condition can withstand is 1.20N.

[0154] Figure 4 This is a macroscopic image of the continuous PGA fiber reinforced ceramic composite bracket prepared in Example 3 of the present invention. Figure 4 a is a physical image of the prepared continuous PGA fiber reinforced ceramic composite scaffold, b is a cross-sectional super-depth image of the continuous PGA fiber reinforced ceramic composite scaffold ×75 times, and c is a cross-sectional super-depth image of the continuous PGA fiber reinforced ceramic composite scaffold ×200 times. Figure 4 As shown in a, the actual picture of the 3D printed continuous PGA fiber reinforced ceramic composite scaffold, the wire diameter is 1000μm, and the scaffold size is 15mm×15mm×6mm. The scaffold has a spacing of 1mm, a smooth surface, good mechanical strength and biodegradability. The scaffold layers are tightly bonded, and no obvious stratification is observed. It can maintain a stable shape during the printing process and is not easy to collapse. Figure 4 As can be seen in b, the ceramic matrix evenly covers the fiber filaments, and the continuous PGA fibers in the ceramic composite scaffold have good concentricity. Figure 4 It can be clearly seen in c that there is a groove left by the continuous fibers in the middle of the cut bracket, which further indicates that its centering is not affected as the printing direction changes, and the continuous PGA fibers have good centering.

[0155] Figure 5 This is a macroscopic image of the continuous PGA fiber reinforced ceramic composite bracket prepared in Example 4 of the present invention. Figure 5 As shown in the figure, the actual picture of the 3D printed continuous PGA fiber reinforced ceramic composite bracket, the wire diameter is 700μm, the size of the bracket is 15mm×15mm×6mm, the bracket adopts a spacing of 0.6mm, the pores are evenly distributed, the pore range is 1mm~2mm, and the Figure 4 The scaffold is similar to the macroscopic image of bracket a in the figure. The scaffold has a smooth surface, tight interlayer bonding, no obvious stratification, and its shape remains stable during the printing process without collapse.

[0156] Figure 6 This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 5 of the present invention. Figure 6 a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire. Figure 6 As shown, it can be seen that the maximum load that the wire prepared under this condition can withstand is 0.95N.

[0157] Figure 7This is a test diagram of the mechanical properties of the continuous PGA fiber composite ceramic wire prepared in Example 6 of the present invention. Figure 7 a is a compression test diagram of the prepared continuous PGA fiber composite ceramic wire, and b is a bending test diagram of the prepared continuous PGA fiber composite ceramic wire. Figure 7 As shown, it can be seen that the maximum load that the wire prepared under this condition can withstand is 1.00N.

[0158] Figure 8 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 1 of the present invention when immersed in Tris-HCl. Fig. 9 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 2 of the present invention when immersed in Tris-HCl. Fig.10 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 3 of the present invention when immersed in Tris-HCl. Fig.11 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 5 of the present invention when immersed in Tris-HCl. Fig.12 This is a graph showing the mass loss of the continuous PGA fiber composite ceramic wire prepared in Example 6 of the present invention when immersed in Tris-HCl.

[0159] Comparing the mass loss graphs of the continuous PGA fiber composite ceramic wires immersed in Tris-HCl in Example 1, Example 2, Example 3, Example 5 and Example 6, it can be seen that the change in the HA whisker content has little effect on the degradation rate of the material, and it is easy to degrade. The Tris-HCl solution is not replaced during the immersion period, and the mass loss rate (slope) gradually decreases after 1 day, and the mass loss is basically stable after 3 days. It shows that the quality has decreased due to the degradation of the wire in the first three days, and with the degradation of the continuous PGA fiber composite ceramic wire, the ion concentration in the Tris-HCl solution increases due to the degradation of the material, reaches saturation, and inhibits further degradation. Therefore, after being immersed in the Tris-HCl solution for 3 days, the quality of the PGA fiber composite ceramic wire no longer changes significantly.

[0160] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0161] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A 3D printing device based on ceramic filaments, characterized in that: include: A wire forming unit, the wire forming unit is used to continuously supply fiber composite ceramic wire (5), the wire forming unit comprises a storage barrel (2), an extrusion device (3) and an extrusion barrel (7), one end of the storage barrel (2) is connected to a power mechanism (1), and the other end is provided with a discharge port (4), the discharge port is communicated with the extrusion device (3), the extrusion device (3) is communicated with the extrusion barrel (7), the upper end of the extrusion barrel (7) is provided with a fiber inlet (9), and the lower end is provided with a nozzle (6); A ceramic wire 3D printing unit, the ceramic wire 3D printing unit is used to extrude and print a fiber composite ceramic wire (5) from a wire forming unit to form a composite ceramic bracket, the ceramic wire 3D printing unit comprises: a wire feeding mechanism and a wire softening printing mechanism, the wire feeding mechanism is used to wind the fiber composite ceramic wire (5) from the wire forming unit and transport it to the wire softening printing mechanism; the wire softening printing mechanism is provided with a softening liquid (13), and the softening liquid ( 13) After softening, extrusion printing is performed to form a composite ceramic bracket; the wire feeding mechanism includes a winder (24), a conduit (23) and a feeding wheel (22), the winder (24) is used to wind the fiber composite ceramic wire (5) from the wire forming unit, one end of the conduit (23) is rotatably connected to the winder (24), and the other end is rotatably connected to the feeding wheel (22), and the feeding wheel (22) is used to transport the fiber composite ceramic wire (5) into the wire softening printing mechanism.

2. A 3D printing device based on ceramic filaments according to claim 1, characterized in that: The wire softening printing mechanism comprises a softening liquid storage device (12), a softening tank (18) and a printing nozzle (19); the softening liquid storage device (12) is connected to the softening tank (18) through a softening liquid pipeline (15); and the printing nozzle (19) is fixedly arranged below the softening tank (18).

3. A 3D printing device based on ceramic filaments according to claim 2, characterized in that: The lower end of the softening liquid pipeline (15) is provided with an extension portion, the lower end of the extension portion is provided with a liquid inlet (17), the liquid inlet (17) is located above the softening tank (18), and the softening liquid pipeline (15) is provided with a flow control valve (16).

4. A 3D printing device based on ceramic filaments according to claim 2, characterized in that: A shearing device (21) is arranged below the outside of the printing nozzle (19), and a three-axis motion platform (20) is arranged below the shearing device (21).

5. A 3D printing device based on ceramic filaments according to claim 2, characterized in that: A fixing block (10) is provided at the upper end of the softening liquid storage container (12), and the fixing block (10) is also connected to a slide rail (11).

6. A method for printing a ceramic bracket, characterized in that: Printing using the 3D printing device according to claim 1 comprises the following steps: Mixing polyvinyl alcohol and a solvent, and heating in a water bath until the polyvinyl alcohol is completely dissolved, to obtain a solution A; After the hydroxyapatite whiskers and the spherical hydroxyapatite are evenly mixed, solution A is added and mixed evenly to obtain a ceramic slurry; Ceramic slurry is added into a storage barrel (2), and then fibers (8) are fed into a nozzle (6) from a fiber inlet (9). The ceramic slurry in the storage barrel (2) is transported into an extrusion device (3) under the action of a power mechanism (1), and then, under the extrusion action of the extrusion device (3), the ceramic slurry is transported into an extrusion barrel (7) through a discharge port (4). After the ceramic slurry and fibers are infiltrated in the nozzle (6) and the slurry uniformly covers the fibers, the fibers are continuously extruded through the nozzle (6) to obtain a fiber composite ceramic wire material (5); The fiber composite ceramic wire (5) is wound and stored by a winder (24), and the wound and stored ceramic wire (5) is continuously transported to a feed wheel (22) through a conduit (23), and the continuous fiber composite ceramic wire (5) is transported to a wire softening printing mechanism via the feed wheel (22), softened by a softening liquid (13) in the wire softening printing mechanism, and then extruded and printed according to a printing path to form a continuous composite ceramic bracket blank; The composite ceramic bracket blank is dried at room temperature and then dried at 50° C. to 70° C. to obtain a continuous fiber composite ceramic bracket.

7. The method for printing a ceramic support according to claim 6, characterized in that: The mass ratio of the polyvinyl alcohol to the solvent is 10:90 to 15:85, and the solvent is water.

8. The method for printing a ceramic support according to claim 6, characterized in that: The length of the hydroxyapatite whisker is 100-200 μm, the aspect ratio is 10-100, the diameter of the spherical hydroxyapatite is less than 100 nm, the mass ratio of the hydroxyapatite whisker to the spherical hydroxyapatite is 3:7-10:0; the mass fraction of polyvinyl alcohol in the ceramic slurry is 15%-5%.

9. The method for printing a ceramic support according to claim 6, characterized in that: The diameter of the fiber composite ceramic wire (5) is 600 μm to 1400 μm.

10. The method for printing a ceramic support according to claim 6, characterized in that: The softening liquid (13) is a PVA aqueous solution, a glycerol aqueous solution, an ethanol aqueous solution or a carboxymethyl cellulose aqueous solution; the drying time at room temperature is 1 hour to 2 hours, and the drying time at 50°C to 70°C is 2 hours to 4 hours.